Biomarkers in cardiomyopathies and prediction of sudden cardiac death - Kruska, Mathieu; El-Battrawy, Ibrahim; Behnes, Michael; Borggrefe, Martin; Akın, Ibrahim (Current pharmaceutical biotechnology, 2017)
Background: Cardiomyopathies are a major cause of heart diseases in all age groups leading to heart failure and arrhythmias. Additionally, they are an important cause of sudden cardiac death (SCD) in young people. Major advances have been made in the understanding of the complex and manifold underlying pathomechanisms and their correlating blood measured biomarkers. The aim of this review is to outline the role of such biomarkers in non-ischemic cardiomyopathies and their role in the prediction of SCD. Methods: A search in bibliographic databases was conducted. Most relevant references focusing on blood measured biomarkers in non-ischemic cardiomyopathies and biomarkers in SCD were reviewed regarding their role in pathophysiology and clinical practice. The references contain prospective and retrospective studies as well as meta-analyses. Current guidelines were analyzed concerning the implementation of biomarkers. Results: Most research on the role of biomarkers in cardiomyopathies is focused on myocardial stress (natriuretic peptides), injury (troponins), inflammation, and remodelling (fibrosis marker). Various studies suggest a potential application of biomarkers in diagnostics, prognosis and treatment response. Further approaches include microRNAs or multimarker approaches. Biomarkers to delineate patients being at risk for SCD have demonstrated predictive ability and could improve risk stratification strategies. Conclusion: To improve the prognosis of cardiomyopathies an early onset of treatment is needed. This necessitates further research and a better integration of biomarkers in the diagnostic work-up of cardiomyopathies. Identification of patients being at risk for SCD is mandatory, however, reliable data of biomarkers are still lacking. Keywords: Biomarker, cardiomyopathy, sudden cardiac death, inflammatory biomarkers, polyunsaturated fatty acids.